PENGARUH SISTEM PENGENDALIAN INTERNAL, PEMANFAATAN TEKNOLOGI, KOMPETENSI SUMBERDAYA MANUSIA DAN PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN SKPA PROVINSI ACEH - Ayang Darmawan; Darwanis Darwanis (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
The research examines the influence of Internal Control System Human Resources Competence, The Use of Information Technology and implementation of local financial accounting system on the Quality of the financial statements. The population in this study is SKPA of Aceh Province. The sampling technique used is simple random sampling. This study uses primary data which obtained through the questionnaire results. Data analysis method used is multiple linear regression. The results shows that Internal Control System have positive and significant effect to Quality of the financial statement, Human Resources Competence have positive and significant effect to Quality of the financial statement, The Use of Information Technology have positive and significant effect to Quality of the financial statement and implementation of local financial accounting system have positive and significant effect to Quality of the financial statement. Keywords: Internal Control System, Human Resources Competence, The Use of Information Technology, implementation of local financial accounting system, Quality of the financial statements